RESERVOIR SIMULATION FOR NATURALLY FRACTURED RESERVOIR TM FIELD DEVELOPMENT - (NIM : 22208046), WIDURI
Naturally fractured reservoir can be found in a lot of place in the world and it has bright future if it is exploited in the right way. TM Field is one of naturally fracture reservoir in Sulawesi marine, which is potential to develop. This reservoir is about 1650 acres and located in the Tomori formation which is dominated with bioclastic limestone. Maximum thickness of the reservoir is about 1469 ft and water oil contact is assumed in 8544 ft. The model given in the simulation is working with double porosity system Warren and Root. There are seven fault which are sealing. The reservoir is in the equilibrium oil and water without presence of gas, the temperature is 212 F and the pressure is 3586 psi. Oil density is 27 API.History match result there is water drive in the system. Reservoir simulation indicates that TM Field reservoir is included in Type III reservoir according to McNaughton and Garb reservoir classification. In that type, storage capacity is in both matrics and fracture system. This reservoir has poor permeability in matrics and viscous oil. So, when the fluid produced and the pressure decline, the water from aquifer is entering the fracture instead the fluid from matrics. Those make the oil recovery of reservoir is note quie qood. If the field is just with the exising producing wells as basecase, oil recovery of TM Field is predicted only 8.7%. The first development is by adding three types of well, vertical, horizontal, and deviated wells. The best result is gained when 5 deviated wells are used, and it produces 46.44% higher. Then, two water injections are added with rate 1000 barrel/day/injector and give 55.52% higher than basecase. The last, gas injector is added ang it gives production 57.34 % higher.